The role of internal governance mechanisms in promoting compliance within ‎the banking sector - Oum-Elkhir Elbaroud; Messaoud Draouissi (Dirassat Journal Economic Issue, 2020)
Given the essential role played by banks in any economy, the application of governance in the banking system is very important to ensure the security of the banking system and the integrity of the stock market and the rest of other institutions.While some bank experts conclude that governance from the banking point of view means the development of internal structures of banks, so as to ensure transparency in execution and improved management, as well as the existence of clear laws determined by banking supervisory and control organizations.This article aims at the relationship between the internal mechanisms of the analysis of banking governance because of the crucial role it plays in promoting effective governance, which bear ultimate responsibility for the internal control systems in banks, and the compliance function with banks.